Links Between Air Quality and Economic Growth Implications for Pittsburgh - Nataraj, Shanthi (RAND Corporation, 2013)
This report assesses the evidence that exists for the ways in which local air quality could influence local economic growth through health and workforce issues, quality-of-life issues, or air-quality regulations and business operations. It then extrapolates some of the existing results to the Pittsburgh region.